How Likely Is a 100-Year Rainfall Event During the Next Ten Years? - Young Gu Her; William R. Lusher; Kati White Migliaccio (EDIS)
This 4-page fact sheet describes proper interpretation of rainfall event probabilities and recurrence intervals, particularly as they are used by engineers and water resources managers in the design and construction of hydraulic structures, such as dams, levees, and canals. This article focuses on rainfall, but its explanations and concepts can be applied to other extreme hydrologic phenomena such as flood and drought. Written by Young Gu Her, William Lusher, and Kati Migliaccio, and published by the UF/IFAS Department of Agricultural and Biological Engineering, March 2018. http://edis.ifas.ufl.edu/ae523